Meningkatkan Daya Dukung Landfill dengan Serbuk Limestone - Andriyani, Utari Wessy; Solichin, Solichin (Department of Civil Engineering, Diponegoro University, 2005)
Laboratories testing to stabilization difficulty soil especially landfill was conducted. As stabilization material are used limestone, with various composition of landfill soil added limestone starting 8 % to 40 % from landfill soil weight. Based on the result testing data can be conclusion that the best composition is landfill soil + 24 % limestone. In this composition the value of ultimate bearing capacity is increase 493.388 % And allawable bearing capacity increasing up to 493.388 %. In this best composition the value of soil parameters: cohesion (Cuu) increase 493,8 %, liquid limitÂ (LL) decrease 12.52 %, OMC decrease 10.8 %, dry unit weight (gd) increase 14.27 %, specific gravity (GS) increase 4.8 % and compression index (Cc) decrease 15,7 %. So that limestone can be used such stabilizationÂ alternative material for landfill.Keywords : Limestone, stabilization, difficult soilPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3918[How to cite: Andriyani, U.W. dan Solichin, 2005, Meningkatkan Daya Dukung Landfill dengan SerbukÂ Limestone, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 3, pp. 13-18]